A Study on Academic Thought and Achievement of Zhang Jingyue in Field of Rehabilitation Medicine - Qinrong SHEN (康复学报)
The paper presents Zhang Jingyue's academic thought and achievement on rehabilitation medicine, which consists of four sections: protective idea for middle aged people, holistic view in terms of tonifying the five internal organs, the conversion relationship between Yin and Yang and the concept that moxibustion and medicine are equally important. It is believed that the academic thought has inheritance as well as innovation and the representative prescription and moxibustion method is simple and inexpensive. He was the master of ancient rehabilitation medical research. Thus, summarizing his clinical experience and studying his academic thought can provide important reference and inspiration for us.